Marcadores nutricionais e inflamatórios e sua associação com a morbimortalidade em hemodiálise - Oliveira, Claudia Maria Costa de (2010)
Background: Malnutrition, inflammation and comorbidities are frequent in patients with chronic renal failure in hemodialysis (HD), contributing for morbidity and mortality. Aims: To evaluate the correlation between anthropometric, laboratory parameters, bioelectrical impedance (BIA) and inflammatory markers with the morbidity and mortality of patients in HD, as well as the impact of its alterations throughout 12 months. Methods: 143 patients of a dialysis facility in Northeast Brazil were evaluated throughout 18 months. Patients with more than 3 months on dialysis, older than 18 years, without amputation of hands and feet, were included in the study. We performed a clinical (subjective global assessment - SGA), anthropometric (BMI, percent of ideal weight, MAC, MAMC, MAMA, percent of fat mass and TSF), laboratory (albumin, creatinine, lymphocyte count as nutritional markers and CRP, IL-6 and TNF- as inflammatory markers) evaluation and BIA (reactance, phase angle and percent of body cell mass) at the beginning of study and after 3, 6 and 12 months of follow-up. The association between study variables and deaths and hospitalizations in 6 and 12 months was investigated. The variable with significance < 10% in the univariate analysis had been enclosed in a multivariate logistic regression analysis. We also investigated the risk of mortality and hospitalization associated with differences in measurements of the variables at baseline and six months later. Results: Patients were aged 52.2 ± 16.6 years on the average, 58% were male, and mean dialysis vintage was 5.27 ± 5.12 years. The prevalence of malnutrition varied from 7.7-63.6%, according to the nutritional marker. The variables associated with morbidity and mortality in 6 and 12 months had been creatinine ≤ 9.45 mg/dl, phase angle ≤ 4.57 degrees, BMI ≤ 23 kg/m2, age ≤ 64.9 years, reactance ≤ 51.7 ohms; Charlson´s index ≥ 4 and socioeconomic status ≤ 7. During six months of follow up, decrease in albumin was associated with significantly higher mortality risk. Conclusions: This study detected that the best predictors of morbidity and mortality between nutritional and inflammatory markers are phase angle, reactance, creatinine and BMI and that changes in albumin values over six 107 months provide additional prognostic information. The authors believe that parameters of BIA may detect early changes in nutritional status and emphasize that longitudinal studies with larger number of patients are necessary to confirm these data and to recommend BIA as a routine nutritional evaluation in HD patients